2014
DOI: 10.1179/1476830514y.0000000120
|View full text |Cite
|
Sign up to set email alerts
|

Nobiletin restores impaired hippocampal mitochondrial bioenergetics in hypothyroidism through activation of matrix substrate-level phosphorylation

Abstract: Nobiletin restores reduced mitochondrial metabolism in hypothyroid rat hippocampus through acceleration of matrix substrate-level phosphorylation that may be important for the prevention of hypometabolic complications in neurological disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
4
1
Order By: Relevance
“…Here, CI plays a role in converting NAD from its reduced form, NADH, www.enjournal.org https://doi.org/10.5607/en20051 Nobiletin for Neuronal Mitochondria to its oxidized form, NAD + , and then synthesizing ATP. Nobiletin was previously reported to recover the reduced ATP metabolism during hypothyroidism in hippocampal mitochondria and activate mitochondrial substrate phosphorylation, indicating that nobiletin may directly or indirectly regulate CI of the ETC system [6]. Unexpectedly, we did not observe the effect of nobiletin to increase mitochondrial viability under CI inhibition (Fig.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…Here, CI plays a role in converting NAD from its reduced form, NADH, www.enjournal.org https://doi.org/10.5607/en20051 Nobiletin for Neuronal Mitochondria to its oxidized form, NAD + , and then synthesizing ATP. Nobiletin was previously reported to recover the reduced ATP metabolism during hypothyroidism in hippocampal mitochondria and activate mitochondrial substrate phosphorylation, indicating that nobiletin may directly or indirectly regulate CI of the ETC system [6]. Unexpectedly, we did not observe the effect of nobiletin to increase mitochondrial viability under CI inhibition (Fig.…”
Section: Discussioncontrasting
confidence: 43%
“…Particularly, positive effects on the nervous system to improve cognitive function and effectively recover motor deficits under pathological conditions such as ischemia, Parkinson' s and Alzheimer' s diseases have been frequently reported [2][3][4]. In its cellular mechanisms, nobiletin regulates the K + influx and the potential (∆Ψ m ) of the mitochondrial inner membrane to prevent mitochondrial calcium overload and neuronal cell death and enhances metabolic rates by changing the mitochondrial matrix substrate [5,6]. These effects suggest that nobiletin may exhibit neuroprotective effects via regulating mitochondrial functions that are associated with the electron transport chain (ETC) system.…”
Section: Introductionmentioning
confidence: 99%
“…The production of oligomycin-insensitive and oligomycin-sensitive ATP in the synaptic and nonsynaptic mitochondria of hippocampus in hypothyroid rats is decreased. These may be counteracted by NOB, which restores disordered mitochondrial metabolism through, at least partially, improving the activities of hexokinase and succinate dehydrogenase [ 30 ]. NOB has been demonstrated to stimulate the synthesis and secretion of catecholamine in bovine adrenal medulla through upregulation of phosphorylation at Ser19 and Ser40 in tyrosine hydroxylase, while downregulating catecholamine synthesis induced by acetylcholine [ 31 ].…”
Section: Nob Exhibits Protection In the Neural Systemmentioning
confidence: 99%
“…In addition, reports have demonstrated that CREB activation is associated with mitochondrial functions (Arnould et al, 2002;Herzig, Scacco, & Scarpulla, 2000;Rim & Kozak, 2002) and that nobiletin regulates mitochondrial function in neuronal cells (Jojua, Sharikadze, Zhuravliova, Zaalishvili, & Mikeladze, 2015;Wu et al, 2013). However, whether nobiletin regulates mitochondrial function in cancer cells is largely unknown.…”
Section: Introductionmentioning
confidence: 99%